MIGRATION IMPLICATIONS OF THE WAR IN UKRAINE ON BOSNIA AND HERZEGOVINA (Security Dialogues, 2024)
Migrations, as a global contemporary phenomenon, take place as a result of various“push-pull factors”, and can have many political, social, cultural or security implications.However, we can state that it is mostly about voluntary migration, while on the other hand,wars as a “push factor” of migration mostly cause forced migration. The war in Ukrainetriggered the largest migration movements in Europe after World War II, because accordingto UNHCR data, 4.8 million refugees from Ukraine were registered for temporary protectionor similar programs in the European Union (EU). However, the question arises as to whattypes of migrations the war in Ukraine triggered, were actually only Ukrainians moving, or asa result of the war were movements of citizens of the Russian Federation recorded as well?The purpose of this paper is to look at the approach of the EU to the war in Ukraine fromseveral different perspectives, the approach of the countries of the Western Balkans (WB),as well as the approach of Bosnia and Herzegovina (BiH). The paper will present the scopeof the migration implications of the war in Ukraine on Bosnia and Herzegovina, through thepresentation of data on the entry, movement, stay and international protection of citizensof Ukraine and citizens of the Russian Federation in Bosnia and Herzegovina. Special focuswill be on the analysis of the reasons for these migrations, and the approach to solving theirstatus will be considered.
Keywords: war, Ukraine, Russian Federation, migrations, refugees, Bosnia and Herzegovina